2012
DOI: 10.1590/s0103-84782012000400013
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de um motor de trator agrícola em bancada dinamométrica com biodiesel de óleo de frango e misturas binárias com óleo diesel

Abstract: RESUMO O Brasil, terceiro maior produtor de biodiesel do mundo e terceiro maior produtor mundial de frango, pode incrementar, na sua matriz energética, o uso de óleo oriundo de aves como alternativa aos combustíveis fósseis e à redução INTRODUÇÃONo Brasil, os combustíveis líquidos representam quase 60% da matriz energética e, destes, 45% são consumidos na forma de óleo diesel (ANP, 2010). Desde 2005, o país fomenta a inclusão gradativa de combustíveis alternativos ao óleo diesel, com ênfase a óleos e gorduras … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
1
3
0
2
Order By: Relevance
“…The agricultural operations in diesel-powered tractors are usually conducted at lower rotations in a working range between 1200 and 2100 rpm (Fiorese et al, 2012), being below the maximum rotation evaluated in this study (3000 rpm), which reinforces the results obtained in the minor rotations, favoring the use of the mixtures used. In this sense, Silveira et al (2013) verified that when using a no-tillage tractor set in no-tillage system in the range of 1500 to 2100 rpm, which the rotation of 1500 rpm provides a reduction of hourly consumption in relation to the maximum rotation, since it is influenced by rotation and speed used in agricultural operations.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The agricultural operations in diesel-powered tractors are usually conducted at lower rotations in a working range between 1200 and 2100 rpm (Fiorese et al, 2012), being below the maximum rotation evaluated in this study (3000 rpm), which reinforces the results obtained in the minor rotations, favoring the use of the mixtures used. In this sense, Silveira et al (2013) verified that when using a no-tillage tractor set in no-tillage system in the range of 1500 to 2100 rpm, which the rotation of 1500 rpm provides a reduction of hourly consumption in relation to the maximum rotation, since it is influenced by rotation and speed used in agricultural operations.…”
Section: Resultssupporting
confidence: 82%
“…Factor that also justifies the effects of improvement in the efficiency of the engine operating with greater proportions of biodiesel, comes from the reduction of the friction of the moving and static parts of the engine, due to the lubrication action that the biodiesel holds, when compared with diesel oil (Fiorese et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Farias et al Some studies showed that there are differences in engine performance parameters when other fuels are used to replace mineral diesel partially or fully. By studying blends with increasing amounts of biodiesel added to mineral diesel, SALA (2008), NIETIEDT et al, (2011), andFIORESE et al (2012) obtained similar engine performance results with regard to torque, power, and specific fuel consumption.…”
Section: Introductionmentioning
confidence: 89%
“…A avaliação da reserva de torque dos motores do ciclo diesel supôs que acima de 15% fosse considerada boa, entre 10 e 15% regular e abaixo de 10% ruim, os critérios de classificação da reserva de torque foram os mesmos estabelecidos por Fiorese et al (2012). A reserva de rotação, expressa em porcentagem, indica a redução da rotação quando a mesma decresce do ponto de potência máxima para o ponto de torque máximo (Equação 3), de acordo com Mialhe (1996).…”
Section: Methodsunclassified